Social Support and Coping of Indonesian Family Caregivers Caring for Persons with Schizophrenia - Rafiyah, Imas; Suttharangsee, Wandee; Sangchan, Hathairat (Department of Nursing, Faculty of Medicine, Universitas Diponegoro, 2011)
Purpose: The aim of the study was to examine the relationship between social support and coping of family caregivers caring for persons with schizophrenia in West Java Province, Indonesia. Methods: This study used the correlational design. Eighty eight family caregivers who cared for persons with schizophrenia were recruited from the Outpatient Department of West Java Province Mental Hospital, West Java, Indonesia through purposive sampling technique. Data were collected by self-report questionnaires using the Perceived Social Support Questionnaire (PSSQ) and the Jalowiec Coping Scale (JCS). Then, data was analyzed by descriptive and Pearson’s product-moment correlation statistic.Results: Overall social support was perceived at a moderate level. The most often coping methods used was optimistic optimistic, followed by self-reliant coping, confrontative coping, and supportant coping. There were significant positive correlation between social support and confrontative coping (r = .68, p < .01), optimistic coping (r = .42, p < .01), and supportant coping (r = .46, p < .01). Social support was significantly and negatively correlate with evasive coping (r = -.52, p < .01) and fatalistic coping (r = -.41, p < .05).Conclusion: For nurses, providing social support including emotional, informational, instrumental, and appraisal support were to be important for caregiver to determine effective coping strategies. Key words: Social support, coping, family caregiver, schizophrenia